The Kinetochore Protein Spc105, a Novel Interaction Partner of LaeA, Regulates Development and Secondary Metabolism in Aspergillus flavus - Zhi, Qing-Qing; He, Lei; Li, Jie-Ying; Li, Jing; Wang, Zhen-Long; He, Guang-Yao; He, Zhu-Mei (Frontiers in Microbiology, 2019)
Nuclear protein LaeA is known as the global regulator of secondary metabolism in Aspergillus. LaeA connects with VeA and VelB to form a heterotrimeric complex, which coordinates fungal development and secondary metabolism. Here, we describe a new interaction partner of LaeA, the kinetochore protein Spc105, from the aflatoxin-producing fungus Aspergillus flavus. We showed that in addition to involvement in nuclear division, Spc105 is required for normal conidiophore development and sclerotia production of A. ﬂavus. Moreover, Spc105 positively regulates the production of secondary metabolites such as aflatoxin and kojic acid, and negatively regulates the production of cyclopiazonic acid. Transcriptome analysis of the spc105 strain revealed that 23 backbone genes were differentially expressed, corresponding to 19 of the predicted 56 secondary metabolite gene clusters, suggesting a broad regulatory role of Spc105 in secondary metabolism. Notably, the reduced expression of laeA in our transcriptome data led to the discovery of the correlation between Spc105 and LaeA, and double mutant analysis indicated a functional interdependence between Spc105 and LaeA. Further, in vitro and in vivo protein assays revealed that Spc105 interacts directly with the S-adenosylmethionine (SAM)-binding domain of LaeA, and that the leucine zipper motif in Spc105 is required for this interaction. The Spc105-LaeA interaction identified in our study indicates a cooperative interplay of distinct regulators in A. flavus, providing new insights into fungal secondary metabolism regulation networks.